Komposisi Gizi, Tingkat Kesukaan dan Daya Terima Moringa Pudding dengan Penambahan 2,5 Gram Bubuk Daun Kelor Pada Balita Stunting - zuhelviyani zainuddin; Hendrayati Hendrayati; Zakaria Zakaria; Sukmawati Sukmawati (Media Gizi Pangan, 2021)
ABSTRACTBackground: Based on Riskesdas in 2018, stunting prevalence on toodlers in Indonesia is 30.8%, South Sulawesi is 13.3% (0-23 months) and 12.5% (0-59 months) and Maros District is 10.37% (severely stunted) and 21.86% (stunted) (Depkes RI, 2018). One of the solutions in handling stunting on toddlers is providing or giving nutritional supplementary food (PMT) such as Moringa Pudding fortified with Moringa Powder. Objective:  This research aims is to find out nutritional values, preference levels test and the receptivity of Moringa Pudding fortified 2.5 gr Moringa Powder on stunted toddlers mothers and stunted toddlers in Majannang village, Maros Baru. Methods: This study is used a pre-experimental design. The sampling technique using purposive sampling. The subject in this study is stunted toddlers aged 24-60 months and stunted toddlers’s mothers. 19 subjects were obtained. Nutritional values were observed using the Nutrisurvey app, preference level test observed using a hedonic test with verbal scale and the receptivity of Moringa Pudding observed using the Comstock method. Results: The nutritional values of Moringa Pudding with 2.5 g Moringa Powder added per 1 serving could fulfill ±10% of the daily intake of toddlers aged 1-5 years based on AKG (2019). 89.5% of panelists were chosen the Like Very Much category for the color aspect. 79% of panelists were chosen Like Very Much category and 10.5% of panelists were choose dislike moderately category for scent aspect on Moringa Pudding. 84.2% of panelists were chosen the Like Very Much category for taste and texture aspect. The receptivity of Moringa Pudding on stunted toddlers was 57.9% for the 100% category. Conclusions: Moringa Pudding fortified 2.5 gram Moringa Powder could fulfill ±10% of the daily intake on toddlers aged 1-5 years and has a good preference levels and receptivity on panelists and stunted toodlers.Keywords: Nutritional Values, Moringa Pudding, Preference Levels, Receptivity, Stunting Toddlers ABSTRAKPendahuluan: Berdasarkan Riskesdas Tahun 2018, prevalensi stunting pada balita di Indonesia sebesar 30,8%, Sulawesi Selatan sebesar 13,3% (0-23 bulan) dan 12,5% (0-59 bulan) dan Kabupaten Maros sebesar 10,37% (sangat pendek) dan 21,86% (pendek) (Depkes RI, 2018). Salah satu solusi dalam mengatasi stunting pada balita adalah dengan menyediakan atau memberikan makanan tambahan (PMT) seperti Moringa Pudding yang difortifikasi dengan bubuk kelor. Tujuan:  Penelitian ini bertujuan untuk mengetahui komposisi gizi, uji tingkat kesukaan dan daya terima Moringa Pudding yang difortifikasi 2,5 gr bubuk kelor pada ibu balita stunting dan balita stunting di Desa Majannang, Maros Baru. Metode: Penelitian ini menggunakan desain pre-eksperimental. Teknik pengambilan subjek menggunakan purposive sampling. Subjek pada penelitian pada penelitian ini adalah balita stunting usia 24 – 60 bulan dan ibu balita stunting. Ditemukan masing-masing sebanyak 19 subjek. Komposisi gizi diamati menggunakan aplikasi Nutrisurvey, uji tingkat kesukaan diamati menggunakan uji hedonik dengan skala verbal dan daya terima Moringa Pudding diamati menggunakan metode Comstock. Hasil: Komposisi gizi Moringa Pudding dengan penambahan 2,5 gr bubuk kelor per 1 takaran saji dapat memenuhi ±10% kebutuhan harian balita usia 1-5 tahun menurut AKG (2019). Sebanyak 89,5% panelis memilih kategori sangat suka untuk aspek warna. Sebanyak 79% panelis memilih kategori sangat suka dan 10,5% panelis memilih kategori tidak suka untuk aspek aroma Moringa Pudding. Sebanyak 84,2% panelis memilih kategori sangat suka untuk aspek rasa dan tekstur. Daya terima Moringa Pudding pada balita stunting sebanyak 57,9% untuk kategori 100%. Kesimpulan: Moringa Pudding yang difortifikasi 2,5 gram bubuk kelor dapat memenuhi 10% kebutuhan harian balita usia 1-5 tahun dan memiliki tingkat kesukaan dan daya terima yang baik pada panelis dan balita stunting.Kata Kunci: Daya Terima, Komposisi Gizi, Moringa Pudding, Tingkat Kesukaan, Balita Stunting